2011
DOI: 10.1007/bf03391652
|View full text |Cite
|
Sign up to set email alerts
|

Social Determinants of Cardiovascular Diseases

Abstract: Social determinants of health can be understood as the social conditions in which individuals live and work; conditions that are shaped by the distribution of power, income and resources, as much on a global and national level as on a local level. Social determinants of cardiovascular diseases are found largely outside the healthcare and preventative healthcare systems; but it is important to think in terms of chains of cause and effect, which enable us to see these determinants at work within the system of cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 62 publications
(60 reference statements)
0
36
0
Order By: Relevance
“…Although the effects of the downstream determinants (genes, personality) on CVD risk factors are clearly evident, the effects of the upstream determinants (policies, societal factors) are less clear [91]. Following are the two main approaches available for the prevention of the cardiovascular diseases.…”
Section: Cvd Prevention Approachesmentioning
confidence: 99%
“…Although the effects of the downstream determinants (genes, personality) on CVD risk factors are clearly evident, the effects of the upstream determinants (policies, societal factors) are less clear [91]. Following are the two main approaches available for the prevention of the cardiovascular diseases.…”
Section: Cvd Prevention Approachesmentioning
confidence: 99%
“…52 On the other hand, numerous studies have found differences in diagnosis and in treatment strategies depending on patient characteristics such as sex, age, and socioeconomic level. 22 Specifically, it has been observed that women are subject to fewer diagnostic tests, are examined less, and receive fewer explanations and less advice from their doctors than men. 53 It is probable that this situation is aggravated if in addition the woman has a lower socioeconomic level.…”
Section: Trends In Socioeconomic Inequalities In Ihd Mortalitymentioning
confidence: 99%
“…may have a relationship with IHD mortality, independently of the individual characteristics of the deceased. 3,[14][15][16][17][18][19][20][21][22] In western European countries, specifically in Spain, a clear decline in IHD mortality has been observed in recent decades. 2,23 This decline is mainly attributed to reductions in the majority of risk factors, such as smoking, hypertension, and hypercholesterolemia, as well as improvements in medical diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Social factors are defined as social life and work conditions, these conditions could be affected by distribution of wealth and power, global and national income (7). A study in China showed the higher risk of metabolic syndrome in women with lower education and monthly income, but male subjects did not reveal this relationship (8).…”
Section: Introductionmentioning
confidence: 99%